Genome sequencing and phylogenetic analysis of 39 human parainfluenza virus type 1 strains isolated from 1997-2010. - Eric T Beck; Jie He; Martha I Nelson; Michael E Bose; Jiang Fan; Swati Kumar; Kelly J Henrickson (PLoS ONE, 2012)
Thirty-nine human parainfluenza type 1 (HPIV-1) genomes were sequenced from samples collected in Milwaukee, Wisconsin from 1997-2010. Following sequencing, phylogenetic analyses of these sequences plus any publicly available HPIV-1 sequences (from GenBank) were performed. Phylogenetic analysis of the whole genomes, as well as individual genes, revealed that the current HPIV-1 viruses group into three different clades. Previous evolutionary studies of HPIV-1 in Milwaukee revealed that there were two genotypes of HPIV-1 co-circulating in 1991 (previously described as HPIV-1 genotypes C and D). The current study reveals that there are still two different HPIV-1 viruses co-circulating in Milwaukee; however, both groups of HPIV-1 viruses are derived from genotype C indicating that genotype D may no longer be in circulation in Milwaukee. Analyses of genetic diversity indicate that while most of the genome is under purifying selection some regions of the genome are more tolerant of mutation. In the 40 HPIV-1 genomes sequenced in this study, the nucleotide sequence of the L gene is the most conserved while the sequence of the P gene is the most variable. Over the entire protein coding region of the genome, 81 variable amino acid residues were observed and as with nucleotide diversity, the P protein seemed to be the most tolerant of mutation (and contains the greatest proportion of non-synonymous to synonymous substitutions) while the M protein appears to be the least tolerant of amino acid substitution.